Formation of the cognitive component of future border guard officers' readiness for physical education of personnel - A. Melnykov; L. Rybak (Kazimierz Wielki University, 2016)
The data on the state of formation of cognitive component of the readiness of future border guard officers to physical education of personnel was obtained and analyzed. The study was attended by 128 cadets of the specialized institution of higher education. The state of formation of the studied component of readiness was determined taking into account the recommendations of experts. In this regard, the criterion of formation of the cognitive component was the assessment for accomplishing of the theoretical part of the physical training exam. It was determined that 71.1% of the cadets achieved the planned result, while the grades of the rest were slightly lower. The obtained data indicated a reserve for improvement, first of all, regarding the approaches to formation and implementation of the content of physical training of future officers of the Border Guard Service during their study in a specialized institution of higher education. This will increase the number of graduates with high and higher than the average levels of cognitive readiness for the physical education of personnel.